PHYSICAL DISTANCING ALARM SYSTEM BASED ON PROXIMITY SENSOR AND MICROCONTROLLER - Yuliza, Elfi; Ekawita, Riska; Vionita, Vionita; Fauzi, Muhammad Khafid; Sari, Vera Fuspita; Rahmayanti, Handika Dany (Indonesian Physical Review, 2021)
Keeping an interaction distance between 1 to 2 m is one of the health protocols during the COVID-19 pandemic. This attempt was made to reduce the spread of the Coronavirus. On the other hand, this health protocol activity is often overlooked, whether intentionally or not. According to the mechanism of the Coronavirus spreading in the form of droplets that comes out during communication, sneezing, or coughing, maintaining distance can be the best effort to minimize the transmission of this virus. Therefore, the availability of a simple, accurate and user-friendly physical distancing alarm system could be a solution in the implementation of this health protocol. In this study, a prototype of a physical distancing alarm based on a distance sensor and a microcontroller in the form of an identity card was developed. Several steps are conducted in developing of this system, namely designing the instrumentation system and testing the performance of the system. System performance is tested through variations in the distance and angle of the objects. The measurement results show that the system can detect objects in front of the sensor up to a distance of 2.8m and an angle of Â for a distance of 1m. The measurement using different angles of objects was performed for objects on the left and right sides of the sensor. In addition, a warning alarm will be on when the distance of the object exceeds the allowed distance. Â